Biodegradable kinetics and behavior of bio-based polyblends under simulated aerobic composting conditions. (1st May 2020) - Kalita, Naba Kumar; Bhasney, Siddharth Mohan; Kalamdhad, Ajay; Katiyar, Vimal
Abstract: The current study evaluates aerobic biodegradation of melt extruded poly(lactic acid) PLA based blends under composting conditions. Samples of neat PLA (NPLA) and bio-based polyblend composites of PLA/LLDPE (linear low-density polyethylene) having different concentration of MCC (microcrystalline cellulose crystal) were analyzed to understand the biodegradation behavior of these blends under simulated composting conditions. Biodegradation kinetics revealed that higher content of MCC and PLA accelerated the biodegradation process of the polymeric blends. Increase in the spherulite growth size and decrease in the spherulite density of the biodegraded samples confirmed the decline in amorphous portion of the test samples due to microbial assimilation, leaving behind the crystalline portion. Surface morphological analysis revealed that the samples of PLA/LLDPE/MCC blends underwent surface erosion prior to bulk biodegradation (50–80%) until the 90th day and the PLA formed fibril-like structures after degradation. This study would help in the design and preparation of biodegradable bio-based commercial blends in the future. Graphical abstract: Image 1095 Highlights: The study showed aerobic biodegradation of PLA/LLDPE/MCC based polyblends. Composting at 58 ± 5 °C was maintained throughout the degradation process. Degradation leads to molecular weight loss of the PLA component in the polyblend. Degradation of only PLA and MCC occurs in the polyblend with LLDPE left behind.